Genocide / Mohamad Sabri Yusoh - Yusoh @ Yusof, Mohamad Sabri (UiTM Kedah, 2003)
This paper contains an imperical study on genocide, quest for a proper definition, historical events and status quo at international level and also the current legal provisions and practices both at national and international arena. It also sought to give possible alternation solution to the prevailing issues.